PERANCANGAN MESIN SHREDDER LIMBAH BOTOL PLASTIK MENGGUNAKAN SENSOR PROXIMITY BERBASIS ARDUINO - Joko Waluyo (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2022)
Abstract The design of this plastic chopping machine is to deal with plastic bottle waste in terminals, stations, airports, bus stops, and hotels. This machine serves to cut plastic bottle waste to a certain size so that the waste can be easily stored so that the waste does not pollute the environment. The machine is designed with an automation system using the Arduino UNO program to facilitate its operation. The purpose of this design is to design a plastic bottle shredder with a capacity of 4000 grams/minute including the design of the shaft diameter, power, gear ratio used and determine the program and sensors used. The method used is technical analysis to determine the load on the shaft so that the specifications of the shaft, motor power can be determined, for the automation system an Arduino-based system is chosen using supporting devices such as relays, and stepdown adapter modules. The results of the engineering design of the plastic chopping machine produced the following machine specifications: 1.5 HP electric motor (220 volts, 1400 rpm), shaft diameter of 30 mm. bearing type 6006 with a life of 2,480,000 hours. Photoelectric type proximity sensor, E3-ZB sensor which features IP67 waterproof capability, with Arduino Uno type. The device supporting this automation system uses the LM2596 Stepdown Module, 30A n Relay Module and a 12v adapter, 220v Pilot Lamp. Keywords: chopping machine, arduino program, automation system, plastic bottle, design